Building climate resilience in Indonesia: The role of cool roofs - Beta Paramita (Field Actions Science Reports)
The urban population in Indonesia is characterized by rapid growth, while urban microclimates are developing in the context of climate change, increasingly having a detrimental impact on human health, especially due to significant heat-related challenges. BeCool's solar reflective paint allows for a cooler surface on painted roofing materials, similar to the effect of wearing white clothes during the day. This innovative technology helps make a concrete contribution to global warming mitigation efforts in Indonesian cities, as it combats the urban heat island effect and its neg impacts, thereby preserving the health of urban dwellers. By reflecting sunlight back into the atmosphere, applying paint can reduce outer surface temperatures by 15°C and inner space temperatures by 3°C, resulting in an 80% reduction in ozone warming.BeCool’s commitment to mitigating global warming extends beyond developing innovative products. The company actively participates in various programs, including painting public buildings, residences, worship and educational buildings. Additionally, BeCool provides education to students across different regions in Indonesia and builds solar reflective houses. These initiatives aim to foster sustainable environmental improvements, ultimately enhancing the health and quality of life within the community.